The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1021/acs.macromol.3c00883
|View full text |Cite
|
Sign up to set email alerts
|

Time–Temperature Superposition of Polybutadiene Vitrimers

Ralm G. Ricarte,
Sachin Shanbhag,
Dana Ezzeddine
et al.

Abstract: A vitrimer has covalent cross-links that preserve network connectivity but permit topology fluctuations through dynamic exchange reactions. In this work, we investigate the linear rheology of polybutadiene (PB) vitrimers bearing cross-links that exchange via dioxaborolane metathesis. PB vitrimers are cross-linked in solution using photoinitiated thiol-ene click chemistry. As the targeted cross-link density is increased, both the insoluble fraction and glasstransition temperature increase. Linear viscoelasticit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 80 publications
0
11
0
Order By: Relevance
“…There is a significant difference in the activation energies estimated from the 1/ e method and from rheological tTS. Apparently, the 1/ e method provided the relaxation time that significantly deviated from the actual value …”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…There is a significant difference in the activation energies estimated from the 1/ e method and from rheological tTS. Apparently, the 1/ e method provided the relaxation time that significantly deviated from the actual value …”
Section: Resultsmentioning
confidence: 90%
“…Apparently, the 1/e method provided the relaxation time that significantly deviated from the actual value. 41 Although we have shown the correct method to estimate the relaxation time, there is one more piece of the puzzle that is still missing because the apparent E a seems to be still higher than the bond energy of the esterification process. 42 Our group has also shown that the segmental relaxation dynamic (τ α ) is non-negligible, and one should consider τ α as the prefactor of bond exchange…”
Section: Viscoelasticity and Dynamic Behaviormentioning
confidence: 85%
“…For the macroscopic rheological properties of vitrimers, neither TTSP nor TESP is applicable, which arises from the complex multiscale dynamic behavior of the material. The experimental results conducted by Ricarte et al also indicate that, with increasing frequency, TTSP fails for the storage modulus of the polybutadiene vitrimers they prepared …”
Section: Resultsmentioning
confidence: 93%
“…Frequency sweep measurements were performed on PUTS5–5% between 140 and 115 °C (Figure A) using a shear strain of 0.4%, which was well within the linear viscoelastic region (LVE-region) of the networks (Figure S19). The frequency sweeps were then combined in a master curve by shifting them toward a reference temperature (140 °C) . To ensure the validity of the time–temperature superposition principle for the materials, van Gurp–Palmen diagrams were first constructed by plotting the phase angle δ as a function of the absolute value of the complex modulus | G *| = ( G ′ 2 + G ′ ′ 2 ) 0.5 (Figure B).…”
Section: Results and Discussionmentioning
confidence: 99%